PENGARUH BEBAN KERJA DAN STRES KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN - ENCEP SAEFULLAH; LISTIAWATI -; ASTI NUR AMALIA (Jurnal Akademika, 2017)
One of the factors that influence the success rate of an organization is employee workproductivity. Efforts to improve employee productivity, among others, is to pay attention tojob stress and workload of employees. This study aims to determine the effect of work stressand workload both simultaneously and partially to the productivity of production employeesin PT.Venia Agape Indonesia.This research is descriptive and associative research with using a quantitative approach. Thesubject of this research is the production employee at PT.Venia Agape Indonesia. Datacollection using questionnaire and scale used is Likert scale. While data analysis is done byusing linear regression analysis and correlation. Based on the results of t test (partial) showsthat the variable X1 (work load) affect the variable Y (work productivity) is shown with thevalue of 4.305> ttable count 0.009 with a contribution of 64.60%. While the variable X2(work stress) affect the variable Y (work productivity) is shown with the value of t count2.029> ttabel 2,009 with a contribution of 54.90%.The results showed Fcount> Ftable (49,684> 3,19) with significance level 0,000 <0,05.This means that workload and job stress simultaneously affect the productivity of work onPT.Venia Agape Indonesia. Based on the calculation of determination coefficient shows RSquare value of 67.40%, it can be concluded that the workload and work stresssimultaneously have a positive and significant effect on employee productivity at theproduction in PT.Venia Agape Indonesia, while the remaining 32.60% is influenced byother variables not described in this study.Keywords: workload, job stress and work productivity